THE IMPACT OF STAGING LAPAROSCOPY ON DIAGNOSIS AND MANAGEMENT OF GASTROINTESTINAL MALIGNANCIES PRESENTING IN A TERTIARY CARE HOSPITAL LAHORE (The Research of Medical Science Review, 2025)
Background: Gastrointestinal malignancies pose a significant health burden, and accurate staging is crucial for optimal treatment planning. While preoperative imaging plays a vital role, it often fails to detect peritoneal disease and occult metastases, leading to inappropriate treatment decisions. Staging laparoscopy (SL) provides a minimally invasive approach to assess disease extent more accurately. Objective: To evaluate the impact of staging laparoscopy on the diagnosis and management of gastrointestinal malignancies in a tertiary care hospital. Study Design & Setting: A descriptive cross-sectional study was conducted at Surgical Unit 1, Sheikh Zayed Hospital, Lahore, over six months. Methodology: Seventy-nine patients with histologically confirmed gastrointestinal malignancies underwent staging laparoscopy after preoperative imaging. Patient demographics, comorbidities, and ECOG/ASA scores were recorded. Preoperative and laparoscopic staging were compared to assess upstaging and treatment modifications. Data were analyzed using IBM SPSS 26. Results: SL upstaged 20% of patients by detecting occult metastases, with peritoneal deposits and liver metastases identified in 23% and 15% of cases, respectively. Post- staging, 28% of patients were shifted to palliative care, and 19% received neoadjuvant therapy. Sensitivity and specificity of SL were 80% and 88.6%, respectively. The procedure had a low complication rate, with 79% of patients experiencing no postoperative complications. Conclusion: Staging laparoscopy significantly improves diagnostic accuracy, prevents unnecessary laparotomies, and optimizes treatment strategies in gastrointestinal malignancies. Its routine integration into staging protocols is recommended.